MEDIA GAMBAR DIGITAL DALAM PEMBELAJARAN BAHASA JERMAN - Apituley, Patresia Silvana; Maruanaya, Rita Fransina; Akihary, Wilma (German für Gesellschaft (J-Gefüge), 2025)
This Community Service activity aims to improve students' vocabulary mastery and speaking skills in learning the German language through the use of digital image media. Vocabulary is a crucial aspect of language acquisition, as it supports both receptive and productive language skills. The activity was conducted online at SMA Negeri 1 Seram Bagian Barat, involving a German language teacher and 30 students. Various teaching methods were applied, including lectures, Q&A sessions, pair work, and group work. The implementation stages included selecting relevant digital image media, introducing vocabulary, speaking practice using Redemittel (useful phrases), group dialogue creation, presentations, and evaluation through quizzes. The use of digital image media proved effective in increasing student interest in learning, enhancing comprehension, expanding vocabulary mastery, and developing German speaking skills. Furthermore, this activity served as guidance for teachers to adopt digital media in their teaching practices independently in the future. By integrating technology creatively and effectively, German language learning becomes more engaging and enjoyable, thereby motivating students to learn actively and continuously.